L'Escultor Arnau Cadell i el claustre de la Seu de Girona - Marquès, Josep Maria (Miscel·lània litúrgica catalana, 2008)
In the Archive of the Diocesis of Girona, among the parchments of the Pia Almoina, the testament of Arnau Cadell has been preserved. This discobering is important because an scription carved next to one of the capitals in the cloister of the monastery of Sant Cugat del Vallès establishes Cadell as its authro, and, moreover, the current stylistical studies put him also in relation with the cloister at Girona Catheral. The testament, dated on 13rd october 1221, gives new data about the death of one of the first catalan artist with known name.